Determinants and outcome of repeat continuous electroencephalogram monitoring—A case‐control study. Issue 4 (23rd September 2019) - Punia, Vineet; Zawar, Ifrah; Briskin, Isaac; Burgess, Richard; Newey, Christopher R.; Hantus, Stephen
Abstract: Objective: A retrospective, single‐center study to analyze the determinants of a repeat continuous EEG (cEEG) monitoring during hospitalization and its outcomes using a matched case‐control study design. Methods: Adults with a repeat cEEG session (cases) were matched by age (±3 years), gender, and mental status to patients with a single cEEG (controls) during hospitalization. Several clinical and EEG characteristics were analyzed to identify predictors of repeat cEEG. Repeat cEEG outcomes were analyzed based on its yield of electrographic seizure. We investigated the predictors of finding increased epileptic potential (degree of association with electrographic seizures) on the repeat cEEG, a marker for possible anti‐epileptic drugs (AEDs) management change. Results: A total of 213 (8.6% of all unique cEEG patients) cases were included. A multivariable conditional logistic regression model comparing cases and controls showed that the presence of acute brain insult [odds ratio (OR) = 3.36, 95% CI = 1.26‐8.94, P  = .015], longer hospital admission (OR = 1.11, 95% CI = 1.07‐1.15, P  < .001) and being on AEDs at the end of index cEEG (OR = 4.0, 95% CI = 1.8‐8.87, P  < .001) was determinants of a repeat cEEG. Among cases, 17 (8%) had electrographic seizures on repeat cEEG. Increased epileptic potential on repeat cEEG was noted in 34 (16%) cases. The latter is associated with change in etiology after the index cEEG ( P  = .03) and duration of repeat cEEG ( P  = .003) based on multivariable logistic regression model. AEDs were changed in 46 (21.6%) patients based on repeat cEEG findings. Significance: Repeat cEEG is not an uncommon practice. It leads to the diagnosis of electrographic seizures in a significant percentage of patients. With the potential of impacting AED management in 16%‐21% patients, it should be considered in high‐risk patients suffering acute brain insults undergoing prolonged hospitalization.